Research on the Design and Analysis Method of the Bird Collision-Resistant Structure of Electric Aircraft Composite Cap-Type-Reinforced Wall Panel-Filled Battery Integration - Yongjie Zhang; Nuo Zhang; Bo Cui; Lei Shi (International Journal of Aerospace Engineering)
Compared with traditional energy aircraft, electric/hybrid aircraft show the advantages of environmental protection and low carbon and have been considered one of the most promising directions for the future development of the aviation industry. However, the battery (battery box) structure employed in electric/hybrid aircraft generally faces several problems (e.g., insufficient rigidity/strength and low structural load-bearing efficiency). In this study, the composite cap-type-reinforced wall plate structure commonly applied in electric aircraft is developed to fill the battery structure using the internal cavity of the cap type, which leads to the formation of an integrated structure type of a composite cap-type-reinforced wall plate filled battery. The basic static strength analysis of the integrated structure was conducted to measure its basic load-bearing capacity. To investigate the impact resistance of the integrated structure, a series of bird collision simulations were conducted to analyze the impact position, impact angle, impact speed, and other factors on the integrated structure and the design direction of the composite cap-type-reinforced wall plate-filled battery-integrated structure against bird collision was summarized.